1995
DOI: 10.1093/ageing/24.5.425
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Home Exercise Programme for Elderly People with Poor Mobility

Abstract: Eighty-six elderly people with limited mobility and dependence in at least one activity of daily living were recruited to a home exercise study. The subjects (mean age 82 years) were allocated at random to either a strength exercise group, a mobility exercise group or a health education group. Subjects were visited for 30 minutes every 3-4 weeks by a physiotherapist who gave both verbal and written instruction. Sixty-nine of the original 86 completed the 6-month study, with five drop-outs from the strength gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 0 publications
1
68
1
Order By: Relevance
“…However, improving muscle strength yields only a small change, sometimes even nonsignificant change, in reducing late-life disability in the outcome of ADL [48,27,26,33,4,10,29,37]. For transfer of physical benefits of resistance strength training to ADL performance seems to be limited.…”
mentioning
confidence: 99%
“…However, improving muscle strength yields only a small change, sometimes even nonsignificant change, in reducing late-life disability in the outcome of ADL [48,27,26,33,4,10,29,37]. For transfer of physical benefits of resistance strength training to ADL performance seems to be limited.…”
mentioning
confidence: 99%
“…A review by Atienza (2001) showed that most empirically examined home-based exercise interventions to date have focused on healthy older adults. Only seven studies were found that specifically targeted frail older adults in the community (Campbell et al, 1997;Gill et al, 2002;Jette et al, 1998;McCool & Schneider, 1999;McMurdo & Johnstone, 1995;Westhoff, Stemmerik, & Boshuizen, 2000;Worm et al, 2001). These interventions varied widely with respect to participant-recruitment strategies, eligibility criteria, exercise prescriptions, and duration (ranging from 2 to 6 months).…”
mentioning
confidence: 99%
“…Physician referrals constituted the typical recruitment strategy. Only four of the protocols were totally home based (Campbell et al;Gill et al;Jette et al, 1998;McMurdo & Johnstone). Four focused exclusively on strength or resistance training (Gill et al;Jette et al, 1998;McCool & Schneider;Westhoff et al).…”
mentioning
confidence: 99%
“…For this reason, exercise training at home or a community center without using strength training equipment has become increasingly in demand by elderly individuals. Some home-based exercise programs have shown benefits to functional abilities in daily activities of elderly individuals (King et al 1991;McMurdo & Johnstone, 1995). It is important to understand how exercise training with using own bodyweight in elderly individuals affects muscle functions that relate to daily activity.…”
Section: Exercise Training For Elderly Individualsmentioning
confidence: 99%